Diversity and regulation of ATP sulfurylase in photosynthetic organisms - Prioretti, Laura; Gontero, Brigitte; Hell, Ruediger; Giordano, Mario (Frontiers in Plant Science, 2014)
ATP sulfurylase (ATPS) catalyzes the first committed step in the sulfate assimilation pathway, the activation of sulfate prior to its reduction. ATPS has been studied in only a few model organisms and even in these cases to a much smaller extent than the sulfate reduction and cysteine synthesis enzymes. This is possibly because the latter were considered of greater regulatory importance for sulfate assimilation. Recent evidences (reported in this paper) challenge this view and suggest that ATPSes may have a crucial regulatory role in sulfate assimilation, at least in algae. In the ensuing text, we summarize the current knowledge on ATPS, with special attention to the processes that control its activity and gene(s) expression. Special attention is given to algae ATPSes. The focus on algae is the consequence of the fact that a comprehensive investigation of ATPSes revealed that the algal enzymes, especially those that are most likely involved in the pathway of sulfate reduction to cysteine, possess features that are not present in other organisms. For instance, algae ATPSes show a great diversity of isoforms and a high content of cysteine residues, whose positions are often conserved. It is interesting that, at least with respect to the number of cysteines, the ATPSes of eukaryotic algae are closer to the marine cyanobacteria of the genera Synechococcus and Prochlorococcus and are more distant from freshwater cyanobacteria. These characteristics might have evolved in parallel with the radiation of algae in the oceans and the increase of sulfate concentration in seawater.